1996
DOI: 10.1099/0022-1317-77-9-2173
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Simian Virus 40 Induces an ERK/MAP Kinase-independent Signalling Pathway that Activates Primary Response Genes and Promotes Virus Entry

Abstract: Simian virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 56 publications
3
67
0
Order By: Relevance
“…Relatively large macromolecules enter cells through either macropinosomes or phagosomes, whereas small molecules (as described earlier) typically enter by clathrin-, caveolarmediated processes, or micropinocytosis. Macropinocytosis is inhibited by amiloride, which blocks the Na + /H + exchanger and inhibits ruffling 85,86 (Figure 2). Macropinocytosis is also dependent on PI3K and Rho GTPase activities, which regulate actin reorganization.…”
Section: Macropinocytosismentioning
confidence: 99%
“…Relatively large macromolecules enter cells through either macropinosomes or phagosomes, whereas small molecules (as described earlier) typically enter by clathrin-, caveolarmediated processes, or micropinocytosis. Macropinocytosis is inhibited by amiloride, which blocks the Na + /H + exchanger and inhibits ruffling 85,86 (Figure 2). Macropinocytosis is also dependent on PI3K and Rho GTPase activities, which regulate actin reorganization.…”
Section: Macropinocytosismentioning
confidence: 99%
“…The protein tyrosine kinase inhibitor, genistein, prevents caveolar endocytosis of SV40 34 and macromolecules, 35 but did not affect perinuclear accumulation of PB although nuclear uptake was inhibited nearly 50%. It is possible that signal modulation through phosphorylation is a partial requirement for nuclear entry.…”
Section: Penton Base Trafficking a Rentsendorj Et Almentioning
confidence: 99%
“…32,33 Perinuclear accumulation was dramatically inhibited by nearly 90% and nuclear accumulation was nearly completely abolished compared to PB uptake without MBCD (Figure 8). To better delineate uptake routes, we treated cells with the protein tyrosine kinase inhibitor, genistein, which prevents caveolae-mediated uptake of SV40 34 and macromolecules. 35 Genistein at 0.1 mM affected PB uptake and perinuclear accumulation a little, whereas nuclear accumulation was inhibited by nearly 50% compared to uptake without the drug ( Figure 8).…”
Section: Effect Of Traffic Inhibitorsmentioning
confidence: 99%
“…We recently reported that SV40 entry is promoted by an intracellular signal that SV40 induces from the cell surface (Dangoria et al, 1996). More recently, we found that signal transmission by SV40 requires the functional integrity of the low-density membrane microdomain that surrounds the caveolae (Y. Chen & L. C. Norkin, unpublished results).…”
Section: Discussionmentioning
confidence: 99%